Inovasi pertunjukan Tunggul Kawung sebagai media pembelajaran seni budaya di Kampung Seni Edas - Arnetha Deyananda; Juju Masunah; Uus Karwati (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the innovation process in the performance packaging of Tunggul Kawung as a community-based arts and culture learning medium at Kampung Seni EDAS. The research employed a qualitative approach using Participatory Action Research (PAR), conducted through two action cycles involving three art practitioners and 15 adolescents aged 13–19. In addition, approximately 50 workshop participants were involved as part of the participatory evaluation process. The research instruments included participatory observation, semi-structured interviews, audio-visual documentation, and a Likert-scale survey. The data were analyzed using Miles and Huberman’s interactive analysis model, which consists of data reduction, data display, and cyclical conclusion drawing. The findings indicate that the innovation was integrated into three main aspects: ergonomic and symbolic instrument design, adaptive musical development aligned with contemporary dynamics, and high-mobility choreography that supports kinesthetic learning. These innovations created a more participatory, inclusive, and meaningful learning experience for adolescents. Furthermore, the study demonstrates how performative innovation in traditional arts can reshape both the cognitive understanding and kinesthetic engagement of learners within the framework of sustainable arts education.